Understanding the reactions of government and gaming concessionaires on COVID-19 through the neo-institutional theory – The case of Macao. (April 2021) - Loi, Kim Ieng; Lei, Weng Si; Lourenço, Fernando
Highlights: Learn from the successful experience of Macao (the world's most densely populated city) in coping with COVID-19. Investigate government's measures and their impact on the hospitality industry. Understand the autonomous behaviours of the gaming concessionaires in coping with this unprecedented crisis. Explain the behaviours of the gaming concessionaires using neo-institutional theory. Abstract: This paper looks at how Macao, the world's most densely populated city, deals with the COVID-19 disease, with a focus on government interventions and responses of the gaming concessionaires who operate integrated resorts. Macao was selected as the case not only because of the background of the authors, but also because Macao has been cited in many media coverage as a "good practice" example when it comes to fighting against this COVID-19 pandemic situation. Since there are already ample of articles on the background, development timeline, and overall commentary, this paper adopts a mixed approach by combining supplementary secondary data on the COVID-19 timeline in Macao (focusing on government interventions that can affect the tourism and hospitality industry) and primary qualitative in-depth interviews with senior management personnel (holding positions of Director or above) from major integrated resorts in Macao to get insights on industry strategic responses and expectation on future. A total of seven interviews were conducted with senior management members of five integrated resorts in May 2020. Four areas of responses were identified. They are 1. Survival; 2. The New Business Norm; 3. Business Rebound Strategies and 4. Corporate Social Responsibility (CSR). The findings indicate a seemingly utopian scenario among the major integrated resorts and gaming concessionaires in Macao towards their compliance and autonomous actions. The mechanism of this utopian-like scenario is explained by adopting the neo-institutional theory.